THE EFFECT OF EDUCATIONAL ATTAINMENT AND WORK EXPERIENCES ON EARNINGS IN INDONESIAN MANUFACTURING SECTORS - Shidiqi, Khalifany Ash; Pasiya, Anggun (Universitas Muhammadiyah Yogyakarta, 2019)
This study examines the effect of educational attainment and work experiences on the earnings of workers from the manufacturing sector in Indonesia. For the last seven years, this sector contributes the most GDP share (approximately more than 20%) compared to other largest sectors, namely agriculture, forestry, and fishery, as well as wholesale and retail trades. Interestingly, the manufacturing sector has the lowest number of workers compared to other mentioned sectors. Based on this comparison, the manufacturing sector likely requires workers who have a good educational background and work experience. Moreover, workers in the manufacturing sector have higher earnings compare to the other two sectors for almost all educational attainments, and its rate is increasing along with the incremental level of education. The study estimates are based on the Mincerian wage equation with a broad cross-section data of the Indonesian Family Life Survey (IFLS) wave 5. The results show that educational attainment and work experiences are significantly and positively correlated with earnings in both urban and rural areas.